Sejarah Perkembangan Pers di Indonesia Ditinjau dari Segi Pendidikan - Iramdhan Iramdhan (Peneliti.net, 2019)
The purpose of this study is to further understand the development of the press in Indonesia from the colonial era to the reform era. The research method uses qualitative research. By collecting secondary data. The press is a social institution and a vehicle for mass communication that carries out journalistic activities including searching, possessing, acquiring, storing, processing, and conveying information in the form of text, images, sound, pictures and sounds, as well as data and graphics and in other forms using media electronics, print media and all types of channels available. The press underwent many changes from time to time, each era has its own characteristics. As a society that gets a lot of information through the press, we should also know the development of the press in Indonesia from the colonial era to the reform era. In terms of education, the Press has a very important role as a means of delivering information that is educational, informative, and educates students to always continue to work and innovate in order to improve the quality of the education system in Indonesia.